Callus induction and bioactive phenolic compounds production from Byrsonima verbascifolia (L.) DC. (Malpighiaceae) - Castro, Ana Hortência; Braga, Karina; Sousa, Fernanda; Coimbra, Mairon; Chagas, Rafael César (Revista Ciência Agronômica, 2015)
This study developed a methodology for callus induction in leaf segments of B. verbascifolia and evaluated the bioactive phenolic compounds production. Leaf explants were cultured in MS medium with 30 g L-1 sucrose, solidified with 7 g L- 1 agar supplemented with 2,4-D (0; 4.52; 9.05; 18.10 μM) and BAP (0; 4.44; 8.88; 17.75 μM ) in the presence and absence of light. Forty-five days after inoculation we assessed the percentage of callus induction, color, consistency, fresh and dry matter, total phenols, flavonoids, tannins contents, and chromatographic profile by HPLC-DAD method. Callus induction occurred only in medium with growth regulators. Maximal induction (100%) was found in medium containing 2,4-D combined with BAP in the presence and absence of light. We obtained friable and compact callus in yellow, green, and red. Culture media containing 4.52 μM 2,4-D + 4.44 μM BAP induced 100% of friable callus with higher fresh and dry weight in the absence of light. The callus produced higher amounts of total phenols and flavonoids than the initial explant. Total tannins were detected only in callus induced in media containing 17.75 μM BAP and 4.52 μM 2,4-D + 17.75 μM BAP, and were not found in the initial explant. The bioactive phenolic compounds detected are derived from benzoic, p-coumaric, cinnamic, gallic acids, and catechins.